III.iv.2. Treatise on the sublime, - Longinus, Dionysius Cassius, 1st cent. (Eliz. Sadleir, 1727)
Originally owned by Henry A. Kennedy and containing numerous manuscript annotations. Inside the front cover are typescript biographical notes on Samuel Armstrong and Henry A. Kennedy, written by Geoffrey Winthrop Young. The notes also explain how the book came into Young's possession from the library of his grandfather, Dr. Evory Kennedy.